2017
DOI: 10.3389/fnagi.2016.00321
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Aβ-Amyloid Estimates by WARM Analysis of [11C]PiB Uptake Distinguish among and between Neurodegenerative Disorders and Aging

Abstract: Background: We report results of the novel Washout Allometric Reference Method (WARM) that uses estimates of cerebral blood flow and amyloid load from the same [11C]Pittsburgh Compound B ([11C]PiB) retention maps in brain to distinguish between patients with different forms dementia, including Alzheimer’s disease, and healthy volunteers. The method introduces two approaches to the identification of brain pathology related to amyloid accumulation, (1) a novel analysis of amyloid binding based on the late washou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The basal ganglia and thalami of patients with AD or MCI, in general, had a higher index of glucose metabolism compared to the cortex. The finding is consistent with the common observation of reduced glucose consumption in patients with AD or MCI, in addition to the hemispheric imbalance revealed by the THGr index [25][26][27][28]. Also, while the decline of metabolism initially may affect only one hemisphere, it progresses to involve both hemispheres but to different degrees.…”
Section: Cerebral Diaschisissupporting
confidence: 90%
See 1 more Smart Citation
“…The basal ganglia and thalami of patients with AD or MCI, in general, had a higher index of glucose metabolism compared to the cortex. The finding is consistent with the common observation of reduced glucose consumption in patients with AD or MCI, in addition to the hemispheric imbalance revealed by the THGr index [25][26][27][28]. Also, while the decline of metabolism initially may affect only one hemisphere, it progresses to involve both hemispheres but to different degrees.…”
Section: Cerebral Diaschisissupporting
confidence: 90%
“…We included the FDG-PET/CT brain images of 23 patients (17 females) with a final diagnosis of AD (n=15) or MCI (n=8), aged 50 to 78 y (mean age 63.7 y). The AD and MCI patients had a mean MMSE score of 20.5 (range: [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 24.9 (range: [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and a mean CAMCOG score of 70.0 (range: 40-98) and 83.8 (range: 60-98), respectively. Ten age-matched HIs aged 43 to 75 y (mean age 62.5 y) were also included (5 females).…”
Section: Resultsmentioning
confidence: 99%
“…For example, early kinetic parameters, such as the unidirectional influx constant (K1), have been shown to be correlated with cerebral blood flow (CBF) and glucose metabolism . Moreover, dynamic data fitted using the simplified reference tissue model (SRTM) have shown that the kinetic parameter R1–the ratio of K1 in target versus a reference tissue is also highly correlated with CBF and glucose metabolism . Associations of early [ 11 C]‐PIB standardized uptake value (SUV) and R1 have recently been validated both with a measure of CBF, [ 15 O]‐water PET, and cerebral glucose metabolism measured with fludeoxyglucose PET .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of the initial phase of the amyloid study to reflect cerebral blood flow (CBF) has been recognized. Reports have compared CBF to estimates derived from the summed early phase [ 11 C]PIB images (6 minutes, 1‐4 minutes), and WARM (washout allometric reference method) and the normalized CBF (to cerebellum) to the R1 parameter from the standard reference tissue model . These techniques are generally computationally demanding (eg, R1 or WARM) or produce relative CBF measures only .…”
Section: Introductionmentioning
confidence: 99%